Towards a common vision of climate, peace, security and migration in Zimbabwe - Caroli, Giulia; De Coning, Cedric; Maviza, Gracsious; Tarusarira, Joram; Minoarivelo , Henintsoa Onivola; Moyo, Nqobile (2024)
Zimbabwe, one of the Southern African countries most affected by climate variability and change, experienced its worst drought in decades this year, impacting over 80% of its population and prompting a national disaster declaration. The increasing frequency and severity of climate impacts are heightening risks to social cohesion, resilience, stability, and peace, complicating the country's security and development landscape. Addressing these challenges requires a multi-stakeholder approach, integrating conflict-sensitivity and peacebuilding into climate policies and actions.